Proses Penetapan Wali Nikah oleh Penghulu terhadap Anak Perempuan yang Dilahirkan Akibat Kehamilan di Luar Perkawinan - Laili, Afrohatul; Nu'man, Moh.; Slamet; Nisa, Irma Naza ‘Aina; Fitria, Lailatul (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2025)
This research examines the process of determining the marriage guardian by the marriage registrar for daughters born from out-of-wedlock pregnancies. Marriage in Islam is a sacred covenant that is clearly regulated, with the guardian being one of the essential pillars that determines the validity of the marriage contract. However, cases of out-of-wedlock pregnancies also referred to as